Konsep Pengelolaan Keuangan Bisnis - Mutiarawan Mutiarawan (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this research is to explain the process of financial management in a business or business carried out by individuals or companies. Qualitative research methods with a library study approach developed by Kuswandi (2005). Data collection techniques with documentation studies taken from books, articles and journals. The data processing technique uses data reduction and presentation, while the data validation technique uses source triangulation. The results of the study show: (1) financial planning, carried out by means of entrepreneurs planning income and financial use in order to achieve an effective and efficient business system. (2) financial recording, carried out by recording all income, expenses, and use of funds in a financial record book. (3) financial reporting, carried out as information and a form of entrepreneur's responsibility for financial conditions while running a business. (4) financial control, which is carried out by assessing and evaluating all forms of financial use so that entrepreneurs know financial conditions and can reduce over-budgeting in each line of business.